Influence of Macrotexture and Microtexture on the Skid Resistance of Aggregates - Bowen Guan; Jiayu Wu; Chao Xie; Jianhong Fang; Haile Zheng; Huaxin Chen (Advances in Materials Science and Engineering)
This article intends to study the influence of macrotexture and microtexture on the skid resistance of four types of aggregates. For this purpose, fractal dimension (D), root mean square height (Rq), and Polished Stone Value (PSV) were tested. The Pearson correlation coefficients between PSV and D or Rq in the interval of different polishing cycles were calculated and analyzed with correlation analysis. The relationships between PSV and Rq were also established. The results showed that the PSV development was approximately divided into 3 stages including accelerated attenuation stage, decelerated attenuation stage, and stabilization stage. There is a critical point of the entire polishing cycles. When the number of the polishing cycles exceeds this critical point, microtexture replaces macrotexture to play a major role in the skid resistance of aggregates. In the accelerated attenuation stage, macrotexture plays a major role in the skid resistance of aggregates. In the decelerated attenuation stage and stabilization stage, microtexture gradually plays a major role in the skid resistance of aggregates. Because of roughest microtexture in the stabilization stage, bauxite can provide the highest levels of skid resistance for high friction surface treatment over the long-term period.